Reading Research Journal Articles in an EFL context: A Pilot Study on Confidence and Difficulty - Ahada, Ichi; Sunggingwati, Dyah; Susilo, Susilo; Rini Setyowati, Dea (Educational Studies: Conference Series, 2023)
This study is based on previous research that compared to textbooks, students find both the style and the level of writing of empirical articles such as research journal articles is difficult to understand. The stages of reading the journal articles are complex. Moreover, there are more studies found in sciences resulted various difficulties but limited research in a foreign language context as the journal articles are written in English. Therefore, there needs an investigation the complexity of reading journal articles to provide some way out to lessen the challenges. As a pilot study for further investigation, a questionnaire was delivered online using google form to 28 students enrolled in the courses of Advanced Reading and Advanced Writing, aged 19-22. They learn to read journal articles in the courses. The given questionnaire consisted of two sections; students self-rated confidence (adapted from Sego and Stuart, 2015) and difficulties in reading comprehension of journal articles (adopted from Chen, 2017). Using simple descriptive statistics, the results revealed that the students have three most major difficulties in reading journal articles, namely short attention span, having a problem understanding the main points, and Limited semantic knowledge (professional terms). They also have three main least challenges; do not know where to start reading, do not understand the tables, charts or statistics, memory failure. The students have the highest confidence in their ability to read and understand the content, however they have the least confidence in their abilities to write coherent summaries of journal articles. The findings imply that the students need to have more time to familiarize themselves with characteristics and construction of journal articles including what should be written in each section of the paper such as introduction, literature review, methodology, findings, discussion, and implication and limitation of the study.